(untitled) (Research in Agriculture Livestock and Fisheries, 2020)
The present study investigated the length-weight relationship, population parameters and the instantaneous natural mortality rate of Arius thalassinus from two major landing center of Bangladesh using the FAO-ICLARM Stock Assessment Tools (FiSAT II). A total of 1789 specimens were collected between January 2016 and December 2017. The estimated values of the exponent “b” was ranged from 3.019 (pre-monsoon) to 3.293 (monsoon), indicating an isometric growth pattern of the species with high correlation coefficients (0.904 to 0.927). The equation of length–weight relationship was: W=0.005L3.181. Model parameters of the von Bertalanffy growth equation were: L∞ = 97.60 cm and K = 0.33-1 year. The estimated growth performance index (Ø) was 3.497. The instantaneous natural mortality rate (M) was 0.62-1 year and a high exploitation rate (E) 0.62 (>0.50) showed that this fish is over-exploited in the Bay of Bengal coast of Bangladesh. Res. Agric., Livest. Fish.6(3): 439-444, December 2019